ANALISIS EFEKTIFITAS DAN EFISIENSI PENERAPAN METODE DAN TEKNOLOGI SMARTDEK DALAM PEKERJAAN PLAT LANTAI BANGUNAN GEDUNG - Yuslan Irianie (INFO-TEKNIK, 2015)
Methods and technologies SMARTDEK an alternative building construction materials as an alternative to conventional methods to work the concrete floor plate which are now widely used in the construction industry.  SMARTDEK use in the construction of the concrete floor plate more practical story buildings without using bakesting when compared to conventional methods that require bakesting and buffer so that if implemented effectively will give efficient in the implementation of good work in terms of the time of execution and in terms of the cost of construction.The writing is trying to conduct studies how far the effectiveness and efficiency of technology implementation SMARTDEK materials used in a building construction gives descriptions of the benefits and application optimization obtained in terms of the aspect of cost and time. In the concrete floor plate work using SMARTDEK, is not necessary to adjust the cutting material SMARTDEK, SMARTDEK dimension to the existing floor plate size field. This is due to the size of SMARTDEK were booked at the factory are adapted to the size of the floor plate that will be done in the field. So after SMARTDEK attached and glue each other, can be directly mounted single reinforcement which then can be done casting. On the other hand consideration cheaper cost and time in the implementation of the concrete floor plate shorter into consideration in choosing the construction of the floor plate by using SMARTDEK.The use of methods and technologies SMARTDEK on a concrete floor plate when compared with the conventional method is more practical or effective and provide efficiency in terms of the aspect of the cost of construction works amounted to 13.89% cheaper, and in terms of aspects of 19.61% job execution time is shorter, thus obtained optimization in its application. Keywords: Methods, Technology, SMARTDEK, Effectiveness, Efficiency, Optimization.